The Need to Enhance the Use of Teleconsultation: A Qualitative Study Among Health Providers to Reduce the Burden of Low Birth Weight - Wiwin Lismidiati; Widyawati Widyawati; Elsi D. Hapsari; Akhmadi Akhmadi; Dimas S. E. W. Sumunar (International Journal of Telemedicine and Applications)
Conclusion: Effectively managing low birth weight requires utilization of technology to strengthen healthcare interventions. Digital solutions enhance communication, broaden service reach, and enable timely support, especially in underserved areas. Incorporating these tools into health programs improves the delivery and accessibility of care, presenting a valuable approach to advancing maternal and child health outcomes.